(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article, the author has conducted research on the development of social entrepreneurship. The relevance and importance of the topic is considered in the works of foreign researchers, some examples of which are given. Entrepreneurship provides a broader understanding of the industry through the business chain. The essence and nature of the approaches to the essence of social entrepreneurship are explained in the table. Shortcomings and problems in this area were mentioned, and the author provided comments and suggestions.